The Role of Psychological and Pedagogical Training of Educators in Establishing Effective Communication with Veterans with Intellectual Disabilities (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
The psychological and pedagogical training of teachers to interact with veterans with signs of intellectual disabilities was identified as a critical factor in post-war social integration. The study aimed to assess the influence of educator preparedness on the quality of communication with veterans in adaptive educational settings.A mixed-methods approach was applied, including surveys, content analysis, pedagogical observations, and correlation analysis. The findings indicated a mismatch between the self-assessed readiness of teachers and veterans' perception of their interactions.A positive relationship was established between educator preparedness and the satisfaction level of veterans. The study contributed to the understanding of how targeted professional training may enhance communication outcomes in education involving vulnerable adult learners.Conclusions pointed to the need for modular training programs tailored to the specific needs of learners with post-traumatic cognitive features.